The British and American Intelligence Divisions in Occupied Germany, 1945–1955 - Daly-Groves, Luke. author. aut Link
XXV, 373 p. 26 illus., 11 illus. in color.
Keywords: “A first-class contribution to the blossoming discipline of Intelligence Studies, taking certain debates and puzzles in fascinating new directions. Empirically and ideationally, this book oozes quality” —Christopher Moran, Professor, University of Warwick, and author of Classified: Secrecy and the State in Modern Britain “The British and American Intelligence Divisions in Occupied Germany, 1945-1955 unearths a trove of new material on Nazi-era and post-war Germany. Intelligence Divisions makes a very strong case for seeing German democracy as the result of relentless work by the Anglo-American secret states. Several sacred cows are slaughtered in the process” —Simon Ball, Professor, University of Leeds, and author of Secret History: Writing the Rise of Britain’s Intelligence Services This book provides the first history of the British and American Intelligence Divisions (IDs) in occupied Germany and the liaison between them. It reveals that after the fall of Adolf Hitler’s Third Reich, much of Germany was controlled by an Anglo-American secret system of rule which was the real backbone of the occupation and largely explains its successful outcomes. Based in Heidelberg, the American ID was the senior American military intelligence organisation in occupied Germany, responsible for the security of American forces in Europe. The British ID, based in Herford, was a purpose-built intelligence organisation designed to ensure the security of the British Zone of Germany and to help achieve the Allied occupation objectives. The IDs undertook military, scientific, security, political, and state-building intelligence tasks which each form the focus of a chapter in this book. Luke Daly-Groves is a Lecturer in Modern European History at the University of Manchester. Prior to this, he lectured at the University of Central Lancashire where he developed a specialist module on modern Germany (1933-1965). He has also taught the history of Germany and secret intelligence at the University of Leeds. In 2021, he was elected as a Fellow of the Royal Historical Society by invitation of the society’s President, in recognition of his contribution to scholarship.